Anazawa, Ishikawa and Kiuchi’s five-type interpretation errors in a legal intepretation in Indonesia - Tunggul Puji Lestari (UPT P2M Politeknik Negeri Malang, 2014)
This study is conducted to examine the generalisability and the coverage of Anazawa, Ishikawa and Kiuchi’s (2012) findings. This study uses real interpretation data taken from a court trial transcript. This study shows the five types of interpretation errors are also found in legal interpretation, as well as in medical interpretation as proved by Anazawa, Ishikawa and Kiuchi. The difference in the frequency is possibly caused by the difference of the field of the study where the interpretation is conducted. It is also found that real data research may cover wider area in interpretation’s errors analysis than simulated scenario research.